1980
DOI: 10.1148/radiology.134.1.7350593
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of the lumbar spinal canal by computed tomography.

Abstract: An experimentally validated simple standardized method for making precise measurements of the spinal canal directly from the video display of a CT scanner is described. Using this method, normal values for anteroposterior diameter, interpediculate distance, and cross-sectional area of the lumbar spinal canal have been determined in a series of 60 adults. A careful study of canal configuration combined with the prudent use of the normal values should allow the CT diagnosis of lumbar spinal stenosis to be made w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
0
5

Year Published

1993
1993
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(96 citation statements)
references
References 0 publications
2
89
0
5
Order By: Relevance
“…The border between cortical bone and soft tissue was clear, and the perimeter of the mandibular cortex could be traced. 21 Hashiba 14 reported that the mandibular volume was significantly larger in skeletal Class I than in Class II, whereas Deguchi et al 16 observed no significant differences among the maxillofacial morphology classifications in 30 adult female Japanese. Our findings in 58 adult male and 60 female Japanese were similar to those reported by this latter study.…”
Section: Discussionmentioning
confidence: 97%
“…The border between cortical bone and soft tissue was clear, and the perimeter of the mandibular cortex could be traced. 21 Hashiba 14 reported that the mandibular volume was significantly larger in skeletal Class I than in Class II, whereas Deguchi et al 16 observed no significant differences among the maxillofacial morphology classifications in 30 adult female Japanese. Our findings in 58 adult male and 60 female Japanese were similar to those reported by this latter study.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have attempted morphometrically to characterize the lumbar spine in individuals with degenerative lumbar spinal stenosis (DLSS) with diverse results [3,[14][15][16][17][18][19][20][21][22]. Some radiological studies have reported that the changes in the anterior-posterior (AP) diameter, transverse diameter and cross-section area (CSA) of the spinal canal and dural sac are risk factors for developing spinal stenosis [16,17,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The CT has become the most used X-ray means. It makes possible a precise measurement of canal dimensions and the diagnosis of the canal narrowness [3]. It has been the imaging means used in our study.…”
Section: Discussionmentioning
confidence: 99%